Leveling up difficulty model based on user experience in education games mobile-based for student kindergartens - Wirawan Istiono (IJNMT (International Journal of New Media Technology), 2020)
The purpose of this study was to identify how to build an educational game model with numerical recognition, numerical ordering and simple counting for kindergarten students with an age range of 3-6 years, where the method used is leveling up difficulty automatically based on user experience, where the level of difficulty will increase based on the success of the user completing the game, the more often the user plays the game, the difficulty level will continue to increase, so hopefully with this model education games mobile-based can develop education games model that can help students recognize numbers and improve their ability to sort and count numbers with more easy and fun way.